Alternative methods of treatment of menopausal syndrome - Ilina I.Yu; Yu.E. Dobrokhotova; D.M. Ibragimova (LCC «Medicine-Inform», 2018)
Alternative methods of treatment of menopausal syndrome Ilyina I.Yu., Dobrokhotova Yu.E., Ibragimova D.M. Pirogov Russian National Research Medical University, Moscow Climacteric period is the transition fr om the reproductive phase of life to the old age. One of the earliest and the most common manifestations of the menopause pathology is climacteric syndrome - a symptom complex characterized by a combination of neuro-psychic, vegetovascular, neuroendocrine disorders. Currently, the method of choice for the treatment of women in menopause is the menopausal hormone therapy (MHT) with the use of natural estrogens or their analogues. Aim: a comparative analysis of menopausal syndrome symptoms in patients who received Feminal and those who did not receive drugs for correction of manifestation of climacteric syndrome in the postmenopausal period. Patients and Methods: 60 women with climacteric syndrome were examined and divided into 2 groups. Patients of group  1 (n = 30) received Feminal orally with food for 1 capsule per day for 3 months. Patients of group 2 (n = 30) did not receive any medications. The severity of the symptoms of menopausal syndrome was assessed in 1 and 3 months after beginning the treatment with Feminal. Results: treatment with Feminal provided a considerable improvement of the patients' well-being, and reduced the MMI (Modified Menopausal Index), which significantly decreased after 3 months of the treatment. Also, after three months of treatment, the number of hot flashes reliably reduced, the number of patients with depressive and anxious condition was lower than in group 2, wh ere the patients had some worsening of symptoms, and the incidence of these symptoms increased. Conclusion: Feminal can be recommended for postmenopausal women who have absolute or relative contradictions for the use of MHT, and for those who doesn't want to use hormonal drugs to reduce the manifestations of menopausal syndrome. Key words: climacteric syndrome, menopause, phytoestrogens, red clover extract, Feminal. For citation: Ilyina I.Yu., Dobrokhotova Yu.E., Ibragimova D.M. Alternative methods of treatment of menopausal syndrome //  RMJ. 2018. № 2(I). P. 8-12.